Komposisi dan Struktur Tegakan Pohon pada Habitat Ungko Lengan Hitam (Hylobates agilis Cuvier, 1821) di Taman Nasional Berbak - Nursanti, Nursanti; Albayudi, Albayudi; Nababan, Marisa (Fakultas Kehutanan Universitas Jambi, 2018)
Dark Handed Gibbon (Hylobates agilis) is one of the wildlife that distribution of seeds by eating fruits. This species categorized as endangered by IUCN (2008) because of habitat destruction in Berbak National Park. This study aims to determine the species composition and structure of tree stand in Hylobates agilis’ habitat in Sungai Rambut Ressort and Sungai Cemara Ressort. The collected data for this study is the tree species, diameter at the breast high (dbh), lateral branches height, total height, crown width, temperature and humidity. Species composition in the study site consists of 56 species and 26 families. The structure of tree stand in Sungai Rambut Ressort showed abnormal condition, while Sungai Cemara Ressort showed a normal habitat with inverted J-shape graph. Keyword: Hylobates agilis, agile gibbon, species composition, tree stand structure, Berbak National Park